Study of Cellular Uptake of Modified Oligonucleotides by Using Time-Resolved Microspectrofluorimetry and Florescence Imaging. Issue 5 (11th July 2012) - Praus Praus, P. P.; Kočišová Kočišová, E. E.; Mojzeš Mojzeš, P. P.; Štěpánek Štěpánek, J. J.; Sureau Sureau, F. F.
Abstract : Fluorescence microimaging and homodyne phase-resolved confocal microspectrofluorimetry were used to monitor the transport of antisense oligonucleotide into cancer MCF7 cells and the subsequent intracellular distribution. Phosphorothioate analog of 15-mer oligoadenylate (dA15 ) labeled by ATTO 425 was complexed with 5, 10, 15, 20-tetrakis (1-methyl-4-pyridyl) porphyrin (H2 TMPyP4) as an uptake-mediating agent. Fluorescence lifetime data within a broad spectral range have revealed properties of both components inside the cell. H2 TMPyP4 lifetime inside the cell is not influenced in this malignant cell line, while the lifetime of modified oligonucleotide was found to be slightly shortened.